Comparison of laboratory parameters of a mountain bike specific performance test and a simulated race performance in the field - Ahrend, M.; Schneeweiss, P.; Theobald, U.; Niess, A. M.; Krauss , I. (Journal of Science and Cycling, 2016)
Previous studies have described the need for a tailored performance test to predict mountain bike performance. This test should improve characterisation of intensive and intermittent physiological demands of mountain biking. Therefore, the aim of the study was to identify mountain bike related parameters that can more accurately explain the variance of mountain bike performance. Ten competitive mountain bike riders (age: 34 ± 8.7 years; VO2peak: 69 ± 11.1 ml·min-1·kg-1) participated in the following tests: (a) an incremental bicycle ergometer test to determine their individual anaerobic threshold (IAT) and maximal oxygen consumption (VO2peak), (b) an isometric strength test, (c) a second bicycle ergometer test consisting of time trials with maximal effort during 10-s, 1-min and 5-min trials and (d) a simulated race in the field. The laboratory parameters were scaled by body weight and subsequently compared with the mean power scaled by body weight and the race time using univariate correlations (rpower; rtime). The incremental test parameters of individual anaerobic threshold (rpower = 0.70; rtime = -0.74) and VO2peak (rpower = 0.85; rtime = -0.86) showed strong correlations with the mean power output during the race and the race time. This result also applies for PO of the laboratory time trials during 1 min (rpower = 0.69; rtime = -0.68) and 5 min (rpower = 0.63; rtime = -0.82). PO of the 10-s time trial (rpower = 0.20; rtime = -0.44), as well as maximal muscle strength (rpower = -0.13; rtime = -0.24), were weakly correlated. In conclusion, power outputs of the 1- and 5-min time trials showed similar correlations with race performance compared with traditional aerobic parameters. These findings underline that traditional aerobic parameters of an incremental test, as well as power output during short high intensive intervals, should be considered when analysing mountain bike performance.